Adolescents as perpetrators of aggression within the family. (July 2016) - Kuay, Hue San; Lee, Sarah; Centifanti, Luna C.M.; Parnis, Abigail C.; Mrozik, Jennifer H.; Tiffin, Paul A.
Abstract: Although family violence perpetrated by juveniles has been acknowledged as a potentially serious form of violence for over 30 years, scientific studies have been limited to examining the incidence and form of home violence. The present study examined the prevalence of family aggression as perpetrated by youths; we examined groups drawn from clinic-referred and forensic samples. Two audits of case files were conducted to systematically document aggression perpetrated by referred youths toward their family members. The purpose of the first audit was fourfold: i) to identify the incidence of the perpetration of family aggression among clinical and forensic samples; ii) to identify whether there were any reports of weapon use during aggressive episodes; iii) to identify the target of family aggression (parents or siblings); and iv) to identify the form of aggression perpetrated (verbal or physical). The second audit aimed to replicate the findings and to show that the results were not due to differences in multiple deprivation indices, clinical diagnosis of disruptive behavior disorders, and placement into alternative care. A sampling strategy was designed to audit the case notes of 25 recent forensic Child and Adolescent Mental Health Service (CAMHS) cases and 25 demographically similar clinic-referred CAMHS cases in the first audit; and 35 forensic cases and 35 demographically similar clinic-referred CAMHS cases in the second audit. Using ordinal chi-square, the forensic sample (audit 1 = 64%; audit 2 = 82.9%) had greater instances of family violence than the clinical sample (audit 1 = 32%; audit 2 = 28.6%). They were more likely to use a weapon (audit 1 = 69%; audit 2 = 65.5%) compared to the clinical sample (audit 1 and 2 = 0%). Examining only the aggressive groups, there was more perpetration of aggression toward parents (audit 1, forensic = 92%, clinical = 75%; audit 2, forensic = 55.17%, clinical = 40%) than toward siblings (audit 1, forensic = 43%, clinical = 50%; audit 2, forensic = 27.58%, clinical = 30%). Based on these findings, we would urge professionals who work within the child mental health, particularly the forensic area, to systematically collect reports of aggression perpetrated toward family members.